2015
DOI: 10.1021/nn506572r
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized Optical and Electronic Detection of Biomolecules Using a Low Noise Nanopore Platform

Abstract: In the past two decades there has been a tremendous amount of research into the use of nanopores as single molecule sensors, which has been inspired by the Coulter counter and molecular transport across biological pores. Recently, the desire to increase structural resolution and analytical throughput has led to the integration of additional detection methods such as fluorescence spectroscopy. For structural information to be probed electronically high bandwidth measurements are crucial due to the high transloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 53 publications
4
55
1
Order By: Relevance
“…To circumvent this problem, single molecule methods have been developed based on either optical or electrical readout. 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this problem, single molecule methods have been developed based on either optical or electrical readout. 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Besides the dielectric properties, photo-induced noise by laser illumination of silicon chips limits their application in combined electronic and optical measurements [37]. Li et al suggested that laser-induced ionic current noise results from a photo-induced electrochemical catalytic process at the interface of the semiconductor and the electrolyte [40].…”
Section: Comparison Of Laser-induced Noise From a Silicon Chip And Frmentioning
confidence: 99%
“…Chips with nanopores for resistive pulse sensing usually consist of a support material with a cavity on one side, which leads to a freestanding membrane containing a nanopore. These freestanding membranes are commonly prepared by thin-film deposition techniques such as low-pressure chemical vapor deposition (LPCVD) or plasma enhanced chemical vapor deposition (PECVD), while the cavities are typically defined using photolithography and formed using dry and wet etching [26,[31][32][33][34][35] or by a membrane transfer technique [36][37][38][39]. Most chips used for nanopore recordings are silicon based [26,31,33,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence is the most likely optical technique to be used in conjunction with a nanopore, but one could imagine that a suitably structured gold film, separated by a well-defined nanopore gap containing an analyte, might also be used for surface-enhanced Raman spectroscopy. 20,27,46,61,90,[267][268][269][305][306][307][308][309][310][311][312][313][314][315] Extensions to Nanopore Arrays. We conclude our discussion of the merging of physical-and optical-based nanopore sensing and manipulation approaches, with the consideration of nanopore arrays.…”
Section: Nanopore As Nanofluidic Cuvette and Optofluidic Devicementioning
confidence: 99%